(untitled) (Bangladesh Journal of Agricultural Research, 2010)
A taxonomic survey was carried out to assess the diversity of plant genetic resources in the Horticultural farm of Bangladesh Agricultural University, Mymensingh. The data were collected during April 2004 to March 2005. A total of 25328 (including unidentified plant species) species were recorded in which trees, shrubs, herbs, climbers and woody grasses were 51.56, 27.60, 7.81, 10.41, and 2.61% of the total species, respectively. The total number of plants belongs to 98 families under 141 genera and 192 species (excluding unknown species). Among these, 65 fruit tree species under 38 genera and 25 families (of which 8 species were rare and endangered), 16 timber plant species under 12 genera and 9 families, 32 medicinal plant species under 29 genera and 24 families (of which 7 species were rate and endangered), 44 ornamental plant species under 34 genera and 25 families (of which 2 species were rare and endangered), 4 spices plant species under 4 genera and 4 families, 11 vegetables plant species under 9 genera and 6 families, 5 bamboo species under 2 genera and one family, 3 rattan (Bet) plant (which were rare and endangered) species under one genus and one family, 10 palm plant species under 10 genera and 2 families, and 2 rubber plant species under 2 genera and one family were recorded. Key Words: Plant diversity; taxonomic survey. DOI: 10.3329/bjar.v34i2.5790 Bangladesh J. Agril. Res. 34(2) : 189-204, June 2009